The etiology of Bell’s palsy: a review - Zhang, Wenjuan; Xu, Lei; Luo, Tingting; Wu, Feng; Zhao, Bin; Li, Xianqi (Journal of neurology, 2020)
Bell’s palsy is the most common condition involving a rapid and unilateral onset of peripheral paresis/paralysis of the seventh cranial nerve. It affects 11.5–53.3 per 100,000 individuals a year across different populations. Bell’s palsy is a health issue causing concern and has an extremely negative effect on both patients and their families. Therefore, diagnosis and prompt cause determination are key for early treatment. However, the etiology of Bell’s palsy is unclear, and this affects its treatment. Thus, it is critical to determine the causes of Bell’s palsy so that targeted treatment approaches can be developed and employed. This article reviews the literature on the diagnosis of Bell’s palsy and examines possible etiologies of the disorder. It also suggests that the diagnosis of idiopathic facial palsy is based on exclusion and is most often made based on five factors including anatomical structure, viral infection, ischemia, inflammation, and cold stimulation responsivity.